Association of atopy and tentative diagnosis of skin cancer – results from occupational skin cancer screenings. (3rd August 2017) - Schäfer, I.; Mohr, P.; Zander, N.; Fölster‐Holst, R.; Augustin, M.
Abstract: Background: The relationship between atopic conditions and carcinoma of the skin has been described inconsistently. Population‐based data providing information on atopic diseases as well as on skin cancer are sparse. Objective: To determine the correlation between atopy and prevalence of precanceroses, non‐melanoma skin cancer and malignant melanoma (MM), while taking into account known risk factors for skin cancer. Methods: Data from occupational skin cancer screenings were analysed in a cross‐sectional study. Dermatologists performed whole body examinations and collected medical histories. Subjects comprised all employees (16–70 years) examined from 2006 to 2014. 'Atopy' was defined by clinical screening diagnosis and/or by participant‐reported, pre‐existing atopic dermatitis, allergic asthma or other specified allergies confirmed by a physician. Tentative screening diagnoses of skin cancer related to actinic keratosis, basal cell carcinoma and malignant melanoma. Results: The study cohort comprised 90 265 employees (mean age 43 ± 11 years, 58.5% male), 30.7% of whom were ever diagnosed with an atopic disease. Persons with atopic conditions recorded in their medical history and at the time of screening had a significantly lower prevalence of actinic keratosis (AK), basal cell carcinoma (BCC) and MM. After controlling for age, sex and relevant risk factors (skin type, childhood sun burns), atopy remained significantly protective against BCC (OR 0.77) and MM (OR 0.53). Conclusion: Design limitations of the study include that all findings of skin cancer were based on clinical examination only and must therefore be considered tentative diagnoses. Furthermore, owing to the cross‐sectional study design, causal pathways cannot be proven. However, analyses of data from such a large and general population‐based cohort afford valuable insights into the relationship between atopic diseases and skin cancer. They provide the grounds for prospective cohort studies to evaluate and dissect the underlying mechanism.